Bullying Behaviour and Victimization among Aboriginal Students within Northwestern Ontario - Brownlee, Keith; Martin, Jaymee; Rawana, Edward; Harper, Julie; Mercier, Monique; Neckoway, Raymond; Friesen, Andrew (First Peoples Child & Family Review, 2014)
This study describes the self-reported bullying experiences and behaviours of Aboriginal students within two schools in a northwestern Ontario community. Different types of bullying and victimization experiences include, but are not limited to: physical, verbal, social, and electronic bullying. These bullying and victimization experiences were assessed among grades 4 through 8 students using the Safe School Survey. The results of the study showed that relative to the entire sample, Aboriginal students reported comparable levels of both victimization and bullying behaviour at school. All students reported verbal bullying behaviours and victimization experiences as the most frequent form of bullying. The results reflected no significant difference between Aboriginal male and female rates of reported bullying and victimization.